2023
DOI: 10.1021/acsbiomaterials.2c00964
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Polyhydroxyalkanoate Blend Electrospun Fibers as Intraluminal Guidance Scaffolds for Peripheral Nerve Repair

Abstract: The use of nerve guidance conduits (NGCs) to treat peripheral nerve injuries is a favorable approach to the current "gold standard" of autografting. However, as simple hollow tubes, they lack specific topographical and mechanical guidance cues present in nerve grafts and therefore are not suitable for treating large gap injuries (30− 50 mm). The incorporation of intraluminal guidance scaffolds, such as aligned fibers, has been shown to increase neuronal cell neurite outgrowth and Schwann cell migration distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…It would be hypothesized that based on its physicochemical properties, NGF would be capable of coassembling with SF in a manner similar to LYS or BLAC and exhibit similar bolus release profiles. The DRG explant model was chosen, as it is routinely used to investigate neurite outgrowth, , which is highly indicative of nerve regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…It would be hypothesized that based on its physicochemical properties, NGF would be capable of coassembling with SF in a manner similar to LYS or BLAC and exhibit similar bolus release profiles. The DRG explant model was chosen, as it is routinely used to investigate neurite outgrowth, , which is highly indicative of nerve regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…[14] We demonstrated a cost-effective, optimized, and scalable method to functionalize glass substrates with NH 2 -presenting groups for peripheral nerve repair, providing substrates with a change in surface wettability, rougher topography, and a lower Young's modulus. [15] This study is the first of its kind to modify PCL fiber scaffolds with 11-aminoundecyl-triethoxysilane for nerve tissue regeneration applications. PCL fiber scaffolds, 10 μm in diameter, were manufactured via electrospinning, confirming fiber diameter and alignment via scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…This study is also the first of its kind to investigate silane-modified substrates using a novel 3D ex vivo fiber testing model using dorsal root ganglion (DRG) explants. [6,7,15] We describe a cost-effective and scalable way to functionalize PCL fibers with NH 2 -presenting groups for nerve repair applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, not only scl-PHAs, but also mcl-PHAs have been investigated for their application in nerve regeneration, due to exhibiting mechanical properties closer to that of native nerve tissue, compared to P(3HB) and FDA-approved polymers PLLA, poly ε-caprolactone (PCL) and PLGA [ 3 , 4 , 14 ]. Homopolymers of poly(3‐hydroxyoctanoate), P(3HO), P(3HB) and their blends were developed and evaluated for their nerve regeneration [ 23 , 24 ]. It was found that both neat polymers and their blends showed high cytocompatibility with respect to the NG108-15 neuronal cell line.…”
Section: Introductionmentioning
confidence: 99%